PROCESS OF INSERTION, MAINTENANCE AND REMOVAL OF PERIPHERAL INTRAVENOUS CATHETERS: PREVENTIVE RISK ANALYSIS - Furlan, Maryana da Silva; Saba, Amanda; Berger, Simone; Lima, Antônio Fernandes Costa (Cogitare Enfermagem, 2023)
Objective: to demonstrate the applicability of the Healthcare Failure Mode and Effect Analysis tool to analyze, preventively, the risks related to the process of insertion, maintenance, and removal of peripheral intravenous catheters. Method: theoretical study, conducted from August to November 2022, in São Paulo-SP, Brazil, whose process was mapped in stages/activities, detailing the failure modes, using the tool. The Risk Priority Number was calculated, the severity and probability matrix was elaborated, adapted to health by DeRosier and collaborators, and actions were proposed to reduce failure modes. Results: The major risks identified were: "perform antisepsis of the area to be punctured with an alcohol swab" and "disinfect the connector with an alcohol swab", and were recommended training and use of kit materials as the main mitigation strategies. Conclusion: knowing the risks associated with peripheral intravenous catheters is the basis for the implementation of preventive strategies, minimizing the occurrence of damage and the associated healthcare costs.